Screening of plants for phytoremediation of oil-contaminated soil. Issue 5 (3rd May 2016) - Ikeura, Hiromi; Kawasaki, Yu; Kaimi, Etsuko; Nishiwaki, Junko; Noborio, Kosuke; Tamaki, Masahiko
ABSTRACT: Several species of ornamental flowering plants were evaluated regarding their phytoremediation ability for the cleanup of oil-contaminated soil in Japanese environmental conditions. Thirty-three species of plants were grown in oil-contaminated soil, and Mimosa, Zinnia, Gazania, and cypress vine were selected for further assessment on the basis of their favorable initial growth. No significant difference was observed in the above-ground and under-ground dry matter weight of Gazania 180 days after sowing between contaminated and non-contaminated plots. However, the other 3 species of plants died by the 180 th day, indicating that Gazania has an especially strong tolerance for oil-contaminated soil. The total petroleum hydrocarbon concentration of the soils in which the 4 species of plants were grown decreased by 45–49% by the 180 th day. Compared to an irrigated plot, the dehydrogenase activity of the contaminated soil also increased significantly, indicating a phytoremediation effect by the 4 tested plants. Mimosa, Zinnia, and cypress vine all died by the 180 th day after seeding, but the roots themselves became a source of nutrients for the soil microorganisms, which led to a phytoremediation effect by increase in the oil degradation activity. It has been indicated that Gazania is most appropriate for phytoremediation of oil-contaminated soil.